2021
DOI: 10.3390/geosciences12010001
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Model to Study the Response of Piles under Lateral Loading in Unsaturated Soils

Abstract: The interaction between a laterally loaded pile and the surrounding soil is typically limited to the shallower soil layer. Often, this zone is above the water table and therefore the interaction takes place under unsaturated conditions. The available evidence is scarce but suggests that unsaturated conditions play a major role on the pile’s response. The actual mechanisms governing the soil–pile interaction under unsaturated soil conditions are not understood entirely, and this paper provides a useful insight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…For the unsaturated soil test, suction stress significantly affected the failure wedge mobilized in front of the pile as it displaced laterally, leading to greater values of lateral resistance on the p-y curves. The results were consistent with those of Lalicata et al [29]. They observed that the lateral resistances along the p-y curve showed an increasing trend in the unsaturated soil condition but were closer to steady lateral resistance values for the fully saturated soil at similar values of lateral displacements.…”
Section: Analysis Of Results and Discussionsupporting
confidence: 92%
“…For the unsaturated soil test, suction stress significantly affected the failure wedge mobilized in front of the pile as it displaced laterally, leading to greater values of lateral resistance on the p-y curves. The results were consistent with those of Lalicata et al [29]. They observed that the lateral resistances along the p-y curve showed an increasing trend in the unsaturated soil condition but were closer to steady lateral resistance values for the fully saturated soil at similar values of lateral displacements.…”
Section: Analysis Of Results and Discussionsupporting
confidence: 92%
“…Less attention has been paid to the effect of unsaturated soil conditions on the response of laterally loaded piles; however, it is well known that pile behavior is greatly affected by the mechanical properties of soil layers near ground surface [1], which is frequently above the water table. To the best of the authors' knowledge, only a few studies [2][3][4][5] have explored the effect of soil suction on the response of laterally loaded piles in unsaturated soils. Mokwa et al [6], for example, proposed a method for calculating the load versus lateral displacement curves for unsaturated soils based on the results of five full-scale load tests.…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of lateral forces is crucial, for example, in the design of tall buildings, bridge abutments, earth-retaining structures and wind turbines. Experimental, analytical and numerical studies show that the response of flexible piles is largely influenced by the pile-soil stiffness ratio whereas, for short and rigid piles, the behaviour is governed by both stiffness and slenderness ratio [1]. The non-linear soil behaviour also strongly influences design parameters such as head displacement, maximum bending moment and critical length.…”
Section: Introductionmentioning
confidence: 99%